CALENDAR -FESTIVAL TEATER INTERKOLE UPM 2008 - New Straits Times (2008)
Festival Tenter Interkolej UPM 2008 is a theatre festival featuring works by the various colleges of Universiti Putra Malaysia (UPM) in Serdang Selangor Venue Panggung Pusat Kebudayaan Dan Kesenian Sultan Salahuddin Abdul Aziz Shah (UPM).